Contributions to EU regional policy - Reconsidering theoretical and empirical perspectives on the Structural Funds - Peter Schmidt (Universität Potsdam, 2016)
This cumulative dissertation contains four self-contained articles which are related to EU regional policy and its structural funds as the overall research topic. In particular, the thesis addresses the question if EU regional policy interventions can at all be scientifically justified and legitimated on theoretical and empirical grounds from an economics point of view. The first two articles of the thesis (“The EU structural funds as a means to hamper migration” and “Internal migration and EU regional policy transfer payments: a panel data analysis for 28 EU member countries”) enter into one particular aspect of the debate regarding the justification and legitimisation of EU regional policy. They theoretically and empirically analyse as to whether regional policy or the market force of the free flow of labour (migration) in the internal European market is the better instrument to improve and harmonise the living and working conditions of EU citizens. Based on neoclassical market failure theory, the first paper argues that the structural funds of the EU are inhibiting internal migration, which is one of the key measures in achieving convergence among the nations in the single European market. It becomes clear that European regional policy aiming at economic growth and cohesion among the member states cannot be justified and legitimated if the structural funds hamper instead of promote migration. The second paper, however, shows that the empirical evidence on the migration and regional policy nexus is not unambiguous, i.e. different empirical investigations show that EU structural funds hamper and promote EU internal migration. Hence, the question of the scientific justification and legitimisation of EU regional policy cannot be readily and unambiguously answered on empirical grounds. This finding is unsatisfying but is in line with previous theoretical and empirical literature. That is why, I take a step back and reconsider the theoretical beginnings of the thesis, which took for granted neoclassical market failure theory as the starting point for the positive explanation as well as the normative justification and legitimisation of EU regional policy. The third article of the thesis (“EU regional policy: theoretical foundations and policy conclusions revisited”) deals with the theoretical explanation and legitimisation of EU regional policy as well as the policy recommendations given to EU regional policymakers deduced from neoclassical market failure theory. The article elucidates that neoclassical market failure is a normative concept, which justifies and legitimates EU regional policy based on a political and thus subjective goal or value-judgement. It can neither be used, therefore, to give a scientifically positive explanation of the structural funds nor to obtain objective and practically applicable policy instruments. Given this critique of neoclassical market failure theory, the third paper consequently calls into question the widely prevalent explanation and justification of EU regional policy given in static neoclassical equilibrium economics. It argues that an evolutionary non-equilibrium economics perspective on EU regional policy is much more appropriate to provide a realistic understanding of one of the largest policies conducted by the EU. However, this does neither mean that evolutionary economic theory can be unreservedly seen as the panacea to positively explain EU regional policy nor to derive objective policy instruments for EU regional policymakers. This issue is discussed in the fourth article of the thesis (“Market failure vs. system failure as a rationale for economic policy? A critique from an evolutionary perspective”). This article reconsiders the explanation of economic policy from an evolutionary economics perspective. It contrasts the neoclassical equilibrium notions of market and government failure with the dominant evolutionary neo-Schumpeterian and Austrian-Hayekian perceptions. Based on this comparison, the paper criticises the fact that neoclassical failure reasoning still prevails in non-equilibrium evolutionary economics when economic policy issues are examined. This is surprising, since proponents of evolutionary economics usually view their approach as incompatible with its neoclassical counterpart. The paper therefore argues that in order to prevent the otherwise fruitful and more realistic evolutionary approach from undermining its own criticism of neoclassical economics and to create a consistent as well as objective evolutionary policy framework, it is necessary to eliminate the equilibrium spirit. Taken together, the main finding of this thesis is that European regional policy and its structural funds can neither theoretically nor empirically be justified and legitimated from an economics point of view. Moreover, the thesis finds that the prevalent positive and instrumental explanation of EU regional policy given in the literature needs to be reconsidered, because these theories can neither scientifically explain the emergence and development of this policy nor are they appropriate to derive objective and scientific policy instruments for EU regional policymakers. – – Diese kumulative Dissertation umfasst vier eigenständige Artikel zur EU-Regionalpolitik und ihren Strukturfonds als dem übergreifenden Forschungsthema der Dissertation. Die Arbeit beschäftigt sich mit der Fragestellung, ob sich aus ökonomischer Sicht die EU-Regionalpolitik überhaupt wissenschaftlich, sowohl empirisch als auch theoretisch, begründen lässt. Die ersten beiden Artikel der Dissertation (“The EU structural funds as a means to hamper migration” und “Internal migration and EU regional policy transfer payments: a panel data analysis for 28 EU member countries”) greifen einen bestimmten Aspekt der Debatte um die Rechtfertigung von Eingriffen der EU-Regionalpolitik in den EU-Binnenmarkt auf. Die beiden Artikel analysieren theoretisch und empirisch, ob die Regionalpolitik oder die freien Marktkräfte in Form von freier Migration im europäischen Binnenmarkt besser geeignet sind, um die Lebens- und Beschäftigungsbedingungen der EU-Bürger zu verbessern und anzugleichen. Basierend auf der neoklassischen Theorie des Marktversagens, argumentiert das erste Papier, dass die Strukturfonds der EU Migration, die einen wesentlichen Mechanismus zur Erreichung von Konvergenz der europäischen Mitgliedsstaaten darstellt, verhindern. Es wird deutlich, dass die EU-Regionalpolitik, welche auf Wachstum und Konvergenz der EU-Mitgliedsstaaten abzielt, nicht gerechtfertigt werden kann, wenn die Strukturfonds Migration in der EU behindern, anstatt sie zu fördern. Der zweite Artikel zeigt jedoch, dass die empirische Evidenz bezüglich des Zusammenhangs von EU-Regionalpolitik und Migration nicht eindeutig ist, d.h. verschiedene empirische Untersuchungen zeigen, dass die Strukturfonds Migration behindern aber auch fördern. Daher ist die Frage der wissenschaftlichen Rechtfertigung der EU-Regionalpolitik auf empirischer Grundlage nicht einfach und eindeutig. Dieses Ergebnis ist unbefriedigend, steht aber im Einklang mit der bisherigen theoretischen und empirischen Literatur. Daher geht die Arbeit an dieser Stelle einen Schritt zurück und überprüft die zu Beginn unterstellte theoretische Grundlage ihrer Analyse der Erklärung und Rechtfertigung der EU-Regionalpolitik, die in der vorherrschenden neoklassischen Marktversagenstheorie zu sehen und zu finden ist. Der dritte Artikel (,,EU regional policy: theoretical foundations and policy conclusions revisited“) behandelt die theoretische Erklärung und Rechtfertigung, als auch die Politikempfehlungen an EU-Regionalpolitiker, welche aus der neoklassischen Marktversagenstheorie abgleitet werden. Der Artikel führt aus, dass das neoklassische Marktversagenskonzept normativ ist und die EU-Regionalpolitik dadurch mit Hilfe eines politischen und damit subjektiven Werturteils rechtfertigt und legitimiert. Dieses Konzept kann jedoch keine wissenschaftlich positive Erklärung der EU-Strukturfonds liefern, noch können daraus objektive und praktisch anwendbare Politikinstrumente abgeleitet werden. Diese Kritik an der neoklassischen Marktversagenstheorie gegeben, stellt das dritte Papier konsequenterweise die vorherrschende Erklärung und Rechtfertigung der EU-Regionalpolitik, welche in der statisch-neoklassischen Gleichgewichtsökonomik geliefert wird, in Frage. Es wird argumentiert, dass eine evolutorische Nicht-Gleichgewichtsperspektive auf die EU-Regionalpolitik wesentlich geeigneter erscheint eine realistische Erklärung für eine der größten Politiken der EU zu geben. Allerdings heißt dies nicht, dass die evolutorische Ökonomik unvoreingenommen als Allheilmittel für eine positive Erklärung und die Ableitung objektiver Politikinstrumente herangezogen werden kann. Warum dies so ist, wird im vierten Artikel der Dissertation (,,Market failure vs. system failure as a rationale for economic policy? A critique from an evolutionary perspective“) diskutiert. Dieser Artikel greift die Erklärung von Wirtschaftspolitik, die aus evolutorischer Perspektive gegeben wird, neu auf. Die neoklassischen Gleichgewichtsvorstellungen des Markt- und Staatsversagens werden mit den vorherrschenden evolutorischen neo-Schumpeterschen und Österreichisch-Hayekiansichen Vorstellungen die Wirtschaftspolitik betreffend verglichen. Auf diesem Vergleich aufbauend kritisiert das Papier, dass neoklassisches Versagensdenken in der evolutorischen Nicht-Gleichgewichtsökonomik weiterhin zu finden ist, wenn wirtschaftspolitische Fragestellungen erörtert werden. Dies ist sehr überraschend, da die Vertreter der evolutorischen Ökonomik ihren Ansatz normalerweise als inkompatibel zu ihrem neoklassischen Pendant ansehen. Der letzte Artikel argumentiert deshalb, dass der Gleichgewichtsgedanke eliminiert werden muss, um die ansonsten sehr fruchtbare und wesentlich realistischere evolutorische Ökonomik vor der Unterminierung ihrer eigenen Kritik an der Neoklassik zu schützen und einen konsistenten als auch objektiven evolutorischen Analyserahmen für wirtschaftspolitische Fragestellungen zu schaffen. Fasst man das Resultat der Dissertation zusammen, bleibt festzuhalten, dass die EU-Regionalpolitik und ihre Strukturfonds aus ökonomischer Sicht weder theoretisch noch empirisch rechtfertigt und legitimiert werden können. Darüber hinaus kommt die Arbeit zu dem Schluss, dass die vorherrschende positive und instrumentelle Erklärung der EU-Regionalpolitik, die in der Literatur gegeben wird, neu gedacht werden muss, da mit Hilfe dieser Theorien weder das Aufkommen und die Entwicklung dieser Politik erklärbar sind, noch geeignete objektive und wissenschaftliche Politikinstrumente für EU-Regionalpolitiker abgeleitet werden können.
urn:nbn:de:kobv:517-opus4-90837
Keywords: 330; EU regional policy; Evolutionary economics; European integration; Market failures; Non-equilibrium economics; System failures; Structural funds; Internal migration; Economic policy